Tinjauan Yuridis Pembatalan Perkawinan Akibat Pemalsuan Identitas Dalam Persepektif Hukum Positif Indonesia: Studi Putusan Nomor 780/Pdt.G/2020/PA.Tmk - Haris, Auliya; Sahruddin, Sahruddin (Private Law, 2024)
This research aims to elucidate the basis of judicial considerations in granting marriage annulment due to identity forgery in Decision Number 780/Pdt.G/2020/PA.Tmk and to explain the legal consequences of marriage annulment due to identity forgery from the perspective of Indonesian positive law. The research method employed is normative legal research. Based on the research findings, it is revealed that the legal basis for the judge's consideration in granting marriage annulment in Decision Number 780/Pdt.G/2020/PA.Tmk is the husband's identity forgery claiming to be a divorced widower, an act which constitutes fraudulent behavior. Additionally, the Panel of Judges evaluated the facts obtained during the trial, relying on the testimonies of witnesses. Based on these witness testimonies, it was established that at the time of marrying the Petitioner, the Respondent was still legally bound in a previous marriage with another woman or his previous wife. Consequently, the marriage between the Petitioner and the Respondent was a polygamous marriage without authorization from the competent Religious Court. Therefore, the Panel of Judges opined that the marriage between the Petitioner and the Respondent should be annulled. Meanwhile, the legal consequences of marriage annulment due to identity forgery consist of the legal consequences regarding the marital relationship and the legal consequences regarding property.